PERAN DIGITALISASI DALAM PERKEMBANGAN IPTEK KEDOKTERAN GIGI SERTA PEMANFAATNYA DI BIDANG PROSTODONSIA - Tri Budi W. Rahardjo (Faculty of Dentistry, Universitas Indonesia, 2015)
Over the next decade, the role of digitalization in dentistry will have a great impact on clinical practice. The implementation of digitalization in dentistry especially in prosthodontics are as follows: computerazied electrodiagnostic instrumentation on stomatognathic system, electronic dental imaging, as well as computer-based knowledge system. To cope with the global competition, the implementation of digitalization in dentistry should be considered by the dentists.